Toxicity of selected newer insecticides against tropical armyworm, Spodoptera litura (Fabricius) - Khairudin, Nur Ashikin (2017)
Tropical armyworm, Spodoptera litura is an insect pest in the family Noctuidae which natively can be found in Asia Pacific region. This pest is considered as an important agricultural pest and the presence of this pest causes many economic losses to the crops. Recently, new insecticides have been introduced into the market. However, the toxicity of these insecticides against S.litura is not well known. A laboratory study was conducted to determine the toxicity of four new insecticides against the early third instar larvae by using leaf dip bioassay technique. Four newer insecticides were spinosad, emamectin benzoate, chlorantraniliprole and indoxacarb. The third instar larvae were exposed to the treated leaves of different concentration of these insecticides and mortality of the larvae was recorded at 24, 48, 72 and 96 and 120 hours after treatment. The data were subjected to Probit Analysis to determine the LC50 values. The order of the toxicity was chlorantraniliprole > emamectin benzoate > indoxacarb > spinosad. The LC50 of chlorantraniliprole was 21.67 μg/ml while spinosad was 234.95 μg/ml. Chlorantraniliprole gave the lowest value of LC50, thus the most toxic against Spodoptera litura.